Mesin Perontok Padi Bagi Kelompok Masyarakat Gotong Royong - Eswanto Eswanto; Muhammad Aulia Rahman; Husni Thamrin (Indonesia Berdaya, 2024)
Farmers cultivating rice fields in Hamlet III Gotong Royong Bukit Lawang Village are farmers who rent rice fields to cultivate and plant rice. There are models of cultivators who rent shares with the owner and there are also those who rent full processing with a rental fee for one harvest of IDR 300,000/1 row of rice fields. The purpose of this PKM is to help solve problems faced by partners by implementing Appropriate Technology independently in hamlet III gotong royong, Bukit Lawang village, especially in terms of: Making and implementing TTG, namely rice harvesting and cleaning/threshing machines needed for rice farmer. The implementation method begins with assessing the lack of technology and equipment in rice harvesting and cleaning/threshing machines, so far the process has been carried out by renting/hiring people who own the machines or done manually, so the method used to achieve the servant objectives is 1). Further surveys at partner locations to find out the working processes of rice harvesting and cleaning/threshing machines and the capacity of the results to be achieved; 2). Design and design of rice harvesting and cleaning/threshing machines using mechanical energy; 3) Manufacture of rice harvesting and cleaning/threshing machines. 4) Test and install rice harvesting and cleaning/threshing machines before giving them to partners. 5) handover of rice harvesting and cleaning/threshing machine units to partners. The community service activities that have been carried out illustrate the importance of the role of universities in applying theoretical knowledge into real practice by applying it directly to communities in need.